2001
DOI: 10.1161/hq0801.093509
|View full text |Cite
|
Sign up to set email alerts
|

NO-Dependent Vasorelaxation Is Impaired After Gene Transfer of Inducible NO-Synthase

Abstract: Abstract-Proinflammatory stimuli produce expression of inducible NO-synthase (iNOS) within blood vessels and are associated with impaired endothelium-dependent relaxation. Gene transfer of iNOS was used to test the hypothesis that expression of iNOS in blood vessels produces impairment of NO-dependent relaxation as well as contraction. An adenoviral vector containing cDNA for murine iNOS, AdCMViNOS, and a control virus, AdCMVBglII, were used for gene transfer to rabbit carotid arteries in vitro and in vivo. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 62 publications
(54 reference statements)
3
49
3
Order By: Relevance
“…A recent study demonstrated that iNOS knock-out mice are resistant to endothelial dysfunction when made diabetic (16). Similarly when the iNOS gene was transferred to normal arteries, NO-dependent relaxation was impaired, suggesting endothelial dysfunction (17). These results strongly suggest a direct involvement of iNOS in endothelial dysfunction in diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study demonstrated that iNOS knock-out mice are resistant to endothelial dysfunction when made diabetic (16). Similarly when the iNOS gene was transferred to normal arteries, NO-dependent relaxation was impaired, suggesting endothelial dysfunction (17). These results strongly suggest a direct involvement of iNOS in endothelial dysfunction in diabetes.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies in vessels exposed to inflammatory cytokines, mice rendered septic using injection of lipopolysaccharide (17) and iNOS gene transfer studies have all supported a role for iNOS-derived NO in causing vascular dysfunction (18,19). If one considers obesity to be an inflammatory condition analogous to low-grade sepsis, iNOS KO mice might be expected to be protected against classical endothelial dysfunction, as has been demonstrated to be the case in sepsis (17).…”
Section: Fig 6 Ros Production and Effect Of Catalase In Inos Ko Micmentioning
confidence: 92%
“…Adenoviral constructs containing inserts of the iNOS isoform gene had full-length (3,690 bp) mouse iNOS cDNA 19 (Gene Bank accession #M87039) inserted into an AdCMV vector following a CMV promoter between Not I and XhoI restriction sites. 20,21 The stock viral concentrations were as follows: Ad5CMVempty, 5.5 Â 10 10 PFU/ml; and Ad5CMViNOS, 2 Â 10 10 PFU/ml. The viruses were suspended in phosphate-buffered saline containing 3% sucrose, aliquoted to 20 ml portions and stored at À808C for further use.…”
Section: Adenovirusmentioning
confidence: 99%